Metal plate having layered double hydroxide on its surface and method for producing same

The high-quality layered double hydroxide (LDH) coating is quickly formed on the surface of magnesium alloy or aluminum alloy by electrodialysis deposition method, which solves the problems of long processing time, high cost and high risk of matrix corrosion in the prior art, and achieves high adhesion, density and controllability coatings.

JP7656958B2Active Publication Date: 2025-04-04NAT INST FOR MATERIALS SCI
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2023505484
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-12
Filing Date
2022-03-03
Publication Date
2025-04-04
Estimated Expiration
2042-03-03

AI Technical Summary

Technical Problem

The prior art layered double hydroxide (LDH) used in surface coatings of magnesium alloys or aluminum alloys has problems such as long-term treatment, high cost, and high risk of matrix corrosion.

Method used

By using the electrodialysis deposition method, by adding metal ions and layered double hydroxide (LDH) powder to the electrolyte, the LDH powder is directly deposited on the metal surface using an electric field to form a high-quality LDH coating.

Benefits of technology

The rapid formation of LDH coatings (1 minute to several minutes) is achieved, which improves the adhesion and density of the coating, reduces the risk of corrosion to the matrix, and allows for free selection of the composition of LDH and the inserted ion or organic molecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656958000006
    Figure 0007656958000006
  • Figure 0007656958000007
    Figure 0007656958000007
  • Figure 0007656958000008
    Figure 0007656958000008
Patent Text Reader

Abstract

[Problem] To provide a method for depositing a film of layered double hydroxide powder of various compositions and metal hydroxides on a metal plate to be processed in a short processing time of one to several tens of minutes. [Solution] The present invention has: steps (S100, S102) of adding metal ions to a water-containing electrolytic solution 16 and dispersing layered double hydroxide powder in the electrolytic solution 16; a step (S104) of immersing an electrode substrate 12 in a suspension comprising the electrolytic solution 16 and the layered double hydroxide powder 40; and steps (S106, S108) of electrodepositing the metal ions in the form of hydroxides together with the layered double hydroxide powder 40 on the electrode substrate 12 by applying an electric field between the electrode substrate 12 and a counter electrode plate. Here, the electrode substrate 12 is a metal plate subject to covering processing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal plate having a layered double hydroxide on its surface and a method for producing the same. [Background technology]

[0002] Magnesium alloys and aluminum alloys are expected to be used as lightweight components for transportation equipment (automobiles, trains, etc.), home appliances, portable electronic devices, and welfare materials (wheelchairs, canes, etc.), but they have a problem of low corrosion resistance, especially in environments containing chloride ions. Transportation equipment and home appliances are exposed to rain, seawater splashes, and human sweat that contain chloride ions. For this reason, the formation of a highly corrosion-resistant coating is required, and depending on the component, painting is required in addition to the highly corrosion-resistant coating. Conventional corrosion-resistant coatings for magnesium materials mainly contain elements with high environmental impact such as chromium, manganese, and fluorine, but as environmental regulations such as RoHS and REACH have been strengthened, the use of chromate treatment has been banned or eliminated. For this reason, there is a demand for corrosion-resistant coatings that are composed of elements that have a small environmental impact during the manufacturing process and are highly safe for the environment during use.

[0003] There has been a report of a highly corrosion-resistant coating formed by anodizing in a solution composed of environmentally friendly elements, mainly phosphoric acid (Patent Document 1). However, anodizing has the disadvantage of consuming a large amount of power. In addition, chemical conversion solutions and anodizing electrolytes containing phosphoric acid, manganic acid, and calcium oxide have been developed (Non-Patent Documents 1 to 4), and the films produced therefrom exhibit high corrosion resistance and adhesion to paint. However, since manganic acid is a substance that requires waste liquid treatment, there is a need for a corrosion-resistant film with even lower environmental impact and a method for producing the same.

[0004] In recent years, layered double hydroxides (LDH: general formula [M 2+ 1-x M 3+ x (OH)2][A n- x / n·mH2O] coatings have attracted attention as corrosion-resistant coatings for magnesium alloys and aluminum alloys (see Patent Documents 2, 3, and 4). LDH is a compound in which a host layer of metal hydroxide layers such as Mg or Al and a guest layer consisting of anions and water molecules are alternately laminated, and it can incorporate not only anions but also organic molecules between the layers. For this reason, it is expected that forming a coating with LDH with a corrosion inhibitor for magnesium alloys or aluminum alloys inserted between the layers will promote self-repair of scratches in the coating. To date, coating formation on the surfaces of AZ31 alloys and Mg-Al-Zn-Ca alloys by autoclave (high temperature / high pressure steam) treatment, coating formation by electrolytic deposition on the surface of AZ91 in metal nitrate solutions such as Zn(NO3)2-Al(NO3)3, coating formation by immersion in LDH slurry and heat treatment, and LDH coating formation by chemical conversion treatment in Al(NO3)3 solution have been performed.

[0005] Autoclave treatment has the advantage of high adhesion because it is a method of growing LDH from the surface of the substrate magnesium alloy, but it takes a long time to process and is costly because a large high-pressure steam furnace must be installed for large components. The slurry immersion method also has the disadvantage of a long processing time. Electrolytic deposition can form a coating in a short time, but the pH of the metal nitrate solution is low, so there is a concern that the substrate may corrode during processing, and there is a problem in applying it to Mg alloys and pure Mg, which have relatively low corrosion resistance. For chemical conversion treatment, a treatment method that can be performed in a relatively short time has been developed, but the composition and form of the LDH layer are highly dependent on the substrate Mg alloy, because the Mg ions eluted from the substrate become the main component of the LDH layer. In addition, whether electrolytic deposition or chemical conversion treatment, it is difficult to insert any anion or organic molecule between the LDH layers after the coating is formed. This is because the ion exchange reaction between the LDH layers takes place in an aqueous solution, so there is a high possibility that the substrate magnesium alloy will corrode during the ion exchange treatment. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5517024 [Patent Document 2] Patent No. 4303948 [Patent Document 3] WO2019-069841 [Patent Document 4] Special table number 2015-520018 [Non-patent literature]

[0007] [Non-Patent Document 1] Shulha, et al., Sci. Rep., 8: 16409 (2018). [Non-Patent Document 2] Wu et al., Appl. Surf. Sci., 313 834 (2014) [Non-Patent Document 3] Light Metals Vol. 67 No. 10 (2017), 511-517 [Non-Patent Document 4] Electrochimica Acta, 283 (2018) 1845-1857 Summary of the Invention [Problem to be solved by the invention]

[0008] Conventional methods for coating the surfaces of magnesium alloys or aluminum alloys with layered double hydroxides (LDHs) have the following problems: the treatment time is long, ranging from several hours to several days; the treatment solution is highly corrosive, limiting the alloy composition that can be treated; the cost is high; and there are limitations on the LDH composition and the ions that can be inserted between the layers. [Means for solving the problem]

[0009] As a result of intensive research, the inventors of the present invention came up with the idea that by using electrophoretic deposition, the processing time can be shortened and the LDH composition and ions that can be inserted between layers can be freely selected. The electrophoretic deposition method is a method in which ceramic particles are charged and dispersed in an electrolyte, an electrode substrate is immersed in the suspension, and an electric field is applied between the counter electrode, thereby directly depositing the ceramic particles on the electrode substrate. The inventors focused on the advantages of electrophoretic deposition, such as the ability to deposit LDH powders of various compositions and the ability to deposit LDH powders with any anion or organic molecule inserted between layers. On the other hand, it is known that the electrophoretic deposition method generally has a problem in adhesion between the ceramic particle deposition layer and the electrode substrate. The inventors discovered that the adhesion of the deposition layer can be improved by adding metal ions to the electrolyte and electrolytically depositing them as hydroxides together with the LDH powder, and thus completed the present invention.

[0010] In other words, the present invention solves the above-mentioned problems and provides a method for forming films of LDH powders and metal hydroxides of various compositions in a short treatment time of about one minute to several tens of minutes, a method for forming a coating containing LDH powder with any anion or organic molecule (inhibitor) inserted between the layers, and a metal plate having a layered double hydroxide on the surface.

[0011] [1] The method for producing a metal plate having a layered double hydroxide on its surface according to the present invention includes the steps of adding metal ions to a water-containing electrolytic solution 16 and dispersing a layered double hydroxide powder in the electrolytic solution 16 (S100, S102), or dispersing a layered double hydroxide powder in a water-containing electrolytic solution 16 and adding metal ions to the electrolytic solution 16 (S102, S100), immersing an electrode substrate 12 and a counter electrode 14 in a suspension of the electrolytic solution 16 containing the added metal ions and layered double hydroxide powder 40 (S104), and applying an electric field between the electrode substrate 12 and the counter electrode 14 to electrodeposit the layered double hydroxide powder 40 and the metal ions on the electrode substrate 12 as hydroxides (S106, S108). Here, the electrode substrate 12 is a metal plate to be coated. Preferably, the method includes a step (S110) of continuing electrophoretic deposition until the film thickness of the layered double hydrate on the electrode substrate 12 reaches a predetermined value.

[0012] [2] In the method [1] for producing a metal sheet having a layered double hydroxide on its surface according to the present invention, the electrolyte 16 is preferably a mixed solvent of an organic solvent and water. [3] In the method [2] for producing a metal sheet having a layered double hydroxide on its surface according to the present invention, the volume ratio of the organic solvent to the water is preferably from 99:1 to 70:30. If the volumetric percentage of water exceeds 30%, corrosion of the magnesium alloy or aluminum alloy substrate in the coating treatment solution increases, and the amount of hydrogen gas generated by the reduction reaction of water increases, resulting in more defects in the coating. If the volumetric percentage of water is less than 1%, the concentration of the organic solvent is too high to obtain the electrical conductivity required for electrophoretic deposition. If the volumetric percentage of water is 1% or more and 30% or less, with the remainder being an organic solvent, a dense layered double hydroxide layer can be produced. [4] In the method [2] or [3] for producing a metal plate having a layered double hydroxide on its surface according to the present invention, the organic solvent preferably includes any one of ethanol, methanol, butanol, ethanol, propanol, isopropanol, glycerin, ethylene glycol, acetone, dimethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diethyl ether, dimethyl sulfoxide, dimethylformamide, and chloroform. [5] In the methods [1] to [4] of the present invention for producing a metal plate having a layered double hydroxide on its surface, the metal ion is preferably any one of Mg, Al, Zn, Mn, Fe, Co, Ni, Cu, Ca, Cr, and In, and the metal salt generating the metal ion is preferably a nitrate, sulfate, carbonate, carboxylate, phosphate, or chloride.

[0013] [6] In the method [1] to [5] for producing a metal plate having a layered double hydroxide on the surface thereof according to the present invention, the layered double hydroxide powder 40 is preferably a compound represented by the general formula: [M 2+ (1-x) M3+ x (OH)2][A n- x / n -yH2O] and M 2+ is a divalent metal ion selected from any one of Mg (magnesium), Zn (zinc), Ca (calcium), Mn (manganese), Pd (palladium), Sr (strontium), Fe (iron), Co (cobalt), Ni (nickel), and Cu (copper), M 3+ is a trivalent metal ion selected from any one of Al (aluminum), Bi (bismuth), Ga (gallium), Ni, Mn, V (vanadium), Ce (cerium), La (lanthanum), Cr (chromium), Fe (iron), Co (cobalt), and In (indium), A is NO3 - ,CO3 2- ,OH - ,Cl - ,SO4 2- ,SiO4 4- or an n-valent (n=1, 2, 3, or 4) anion selected from any one of phosphate, chromate, permanganate, vanadate, selenate, borate, fluoride, carboxylate, stannate, aluminate, and molybdate. [7] In the method for producing a metal plate having a layered double hydroxide on the surface thereof according to the present invention [6], preferably, the trivalent metal ions in the layered double hydroxide powder 40 are mixed with divalent metal ions at a maximum molar ratio M 2+ :M 3+ It is recommended to replace up to 2:1. 3+ When the ratio of is zero, it is called Mg(OH)2 (brucite). The lower limit is a state where no substitution is present, but the molar ratio of divalent to trivalent metal ions is preferably in the range of 4:1 to 2:1.

[0014] [8] In the methods [6] to [7] for producing a metal plate having a layered double hydroxide on its surface according to the present invention, the volume ratio of layered double hydroxide powder 40 to metal hydroxide in the deposited layer electrodeposited on the electrode substrate 12 is preferably layered double hydroxide powder:metal hydroxide=90:10 to 10:90. The volume ratio of the layered double hydroxide powder and the metal hydroxide in the sediment layer is explained below. The upper limit of the powder ratio is layered double hydroxide powder:metal hydroxide = 90:10 (volume ratio). This is because the maximum packing ratio is about 90% in a simulation in which two types of lenticular particles of different sizes are mixed randomly. The lower limit of the widest range is layered double hydroxide powder:metal hydroxide = 10:90 (volume ratio). This is the ratio in a sediment layer created by EPD at a low voltage or in an electrolyte with a low metal ion concentration. The lower limit of the preferred range is layered double hydroxide powder:metal hydroxide = 55:45 (volume ratio). This is because the lowest packing ratio is about 55% in a simulation in which uniformly sized spherical particles are randomly packed. The lower limit of the more preferred range is layered double hydroxide powder:metal hydroxide = 68:32 (volume ratio). This is the case in which the layered double hydroxide powder is uniformly sized and spherical and packed in a body-centered cubic configuration. The lower limit of the optimum range is layered double hydroxide powder:metal hydroxide = 74:26 (volume ratio), in which the layered double hydroxide powder is packed closely in the form of uniformly sized spheres, with the metal hydroxide filling the gaps. Widest range: Layered double hydroxide powder: Metal hydroxide = 90:10~10:90 Preferred range: layered double hydroxide powder: metal hydroxide = 90:10 to 55:45 More preferable range: 90:10 to 68:32 Optimum range: Layered double hydroxide powder: Metal hydroxide = 90:10~74:26 [9] In the methods [1] to [8] for producing a metal plate having a layered double hydroxide on its surface according to the present invention, the electrode substrate 12 is preferably any one of pure Mg material, pure Al material, pure Fe material, AZ31 (Mg-3Al-1Zn) alloy, AZ91 (Mg-9Al-1Zn) alloy, AM60 (Mg-6Al-0.4Mn) alloy, AXM (Mg-Al-(Zn)-Ca) alloy, WE43 (Mg-4Y-3RE) alloy, ZK60 (Mg-6Zn-0.5Zr) alloy, 5000 series Al alloy (Al-Mg), 6000 series Al alloy (Al-Mg-Si), 7000 series Al alloy (Al-Zn-Mg) alloy, and carbon steel.

[10] In the methods [1] to [9] for producing a metal plate having a layered double hydroxide on its surface according to the present invention, the electric field applied to the electrode substrate 12 is preferably a pulse voltage or a constant voltage.

[0015]

[11] The metal plate having a layered double hydroxide on its surface according to the present invention is a metal plate having a layered double hydroxide on its surface, the layered double hydroxide being a mixed deposited coating of layered double hydroxide powder and metal hydroxide, and the thickness of the mixed deposited coating is 0.5 μm or more and 130 μm or less.

[12] In the metal plate having a layered double hydroxide on a surface thereof

[11] of the present invention, the metal plate is preferably made of pure Mg, pure Al, pure Fe, AZ31 (Mg-3Al-1Zn) alloy, AZ91 (Mg-9Al-1Zn) alloy, AM60 (Mg-6Al-0.4Mn) alloy, AXM (Mg-Al-(Zn)-Ca) alloy, WE43 (Mg-4Y-3RE) alloy, ZK60 (Mg-6Zn-0.5Zr) alloy, 5000 series Al alloy (Al-Mg), 6000 series Al alloy (Al-Mg-Si), 7000 series Al alloy (Al-Zn-Mg) alloy, or carbon steel.

[13] In the metal plate

[11] or

[12] having the layered double hydroxide on its surface according to the present invention, the volume ratio of the layered double hydroxide powder to the metal hydroxide in the mixed deposited coating of the layered double hydroxide powder and the metal hydroxide is preferably layered double hydroxide powder:metal hydroxide=90:10 to 10:90. Effect of the Invention

[0016] In the method of manufacturing a metal plate having a layered double hydroxide on its surface according to the present invention, the effect of electrophoretic deposition of layered double hydroxide powder in an electrolyte solution containing a metal nitrate as the metal ion added thereto will be explained in comparison with the prior art. 1) Layered double hydroxide powder is used as the main raw material. This allows for a high degree of freedom in the composition of the layered double hydroxide powder and the anions and organic molecules between the layers. 2) Electrophoretic deposition is a technique that can form a coating that is several micrometers thick or thicker in a relatively short time, so the coating time can be shortened. 3) Electrophoretic deposition can form layered double hydroxide films regardless of the alloy composition. In contrast, chemical conversion coating and autoclave treatment incorporate Mg and Al from the magnesium alloy substrate into the coating to form layered double hydroxides, so the composition of the coating depends on the composition of the substrate alloy. 4) When metal nitrates are added to the electrolyte as metal ions as in the examples, the method combines electrolytic deposition and electrophoretic deposition. The simultaneous precipitation and deposition of metal hydroxide and layered double hydroxide powders can improve the adhesion of the powders.

[0017] According to the metal plate having the layered double hydroxide of the present invention on the surface thereof, the coating exhibits corrosion resistance, and thus has the effect of suppressing corrosion of the metal plate. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram of an electrophoretic deposition apparatus used for producing a metal plate having the layered double hydroxide of the present invention on its surface. [Diagram 2] 1 is a flow chart illustrating a process for producing a metal plate having a layered double hydroxide on the surface thereof according to the present invention. [Diagram 3] Electron microscope images of AZ31 surfaces subjected to electrophoretic deposition (EPD) in ethanol-water electrolytes containing only hydrotalcite (HT) powder at various concentrations. [Figure 4]Electron microscope images of AZ31 surfaces subjected to electrophoretic deposition (EPD) of hydrotalcite (HT) powder in ethanol-water electrolytes containing various concentrations of Mg and Al ions. [Figure 5A] Figure 1 shows the X-ray diffraction patterns of AZ31 surfaces subjected to electrophoretic deposition (EPD) in ethanol-water electrolyte containing hydrotalcite (HT) powder with various concentrations of Mg and Al ions, with the addition of Mg or Al ions. [Figure 5B] Figure 1 shows the X-ray diffraction patterns of AZ31 surfaces subjected to electrophoretic deposition (EPD) in ethanol-water electrolyte containing hydrotalcite (HT) powder with various concentrations of Mg and Al ions, with the addition of Mg and Al ions. [Figure 6] 1 shows the relationship between the thickness of the mixed deposition layer and the total concentration of Mg ions and Al ions in the electrolyte. [Figure 7] The results of wet and dry cycle tests on the HT-metal hydroxide mixed deposit surface are shown. [Figure 8A] These are photographs of the appearance of a treated metal plate, which was subjected to electrophoretic deposition (EPD) in an ethanol-water electrolyte containing Mg ions and Al ions containing hydrotalcite (HT) powder, before and after a wet-dry cycle test. The photograph shows a pure Mg plate. [Figure 8B] The photographs show the appearance of a treated metal plate, which was subjected to electrophoretic deposition (EPD) in an ethanol-water electrolyte containing Mg ions and Al ions with hydrotalcite (HT) powder, before and after a wet-dry cycle test. The photograph shows an AZ31 plate. [Figure 9] Electron microscope image of an AZ31 surface subjected to electrophoretic deposition (EPD) at a constant voltage in an isopropanol-water electrolyte containing Mg ions. [Figure 10] These are electron microscope images of the surfaces of pure Al and pure Fe, which were subjected to electrophoretic deposition (EPD) in an electrolyte containing a suspension of Mo-intercalated layered double hydroxide (MoLDH) powder. [Figure 11]These are electron microscope images of the surfaces of pure Al and pure Fe subjected to electrophoretic deposition (EPD) in an electrolyte containing a suspension of hydrotalcite (HT) powder. [Figure 12] These are X-ray diffraction patterns of the surfaces of pure Al and pure Fe, which were subjected to electrophoretic deposition (EPD) in an electrolyte containing a suspension of Mo-intercalated layered double hydroxide (MoLDH) powder. [Figure 13] These are X-ray diffraction patterns of pure Al and pure Fe surfaces subjected to electrophoretic deposition (EPD) in an electrolyte containing a suspension of hydrotalcite (HT) powder. [Figure 14] These are photographs of the appearance of pure Al and pure Fe coated with MoLDH or HT after repeated wet and dry tests. [Figure 15] 1 is a graph showing the weight change before and after repeated wet-dry tests of (a) pure Al and (b) pure Fe coated with MoLDH or HT. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0019] The present invention will now be described with reference to the drawings. Fig. 1 is a schematic diagram of an electrophoretic deposition apparatus used to produce a metal plate having the layered double hydroxide of the present invention on its surface. In Fig. 1, the electrophoretic deposition apparatus comprises an electrolytic cell 10, a stirrer 20, a DC power supply 30, and a function generator 36. The electrolytic cell 10 contains a surface treatment solution 16 in which a substrate 12 as a metal substrate to be treated and a counter electrode plate 14 are immersed, and a stirrer 22 is positioned below the surface treatment solution 16. As treatment by electrophoretic deposition progresses, metal hydroxide 18 is deposited on the surface of the substrate 12.

[0020] One pole of the DC power supply 30 is connected to the substrate 12 by an electric wire 32. The other pole of the DC power supply 30 is connected to the counter electrode plate 14 by an electric wire 34. Due to the potential difference generated between the substrate 12 and the counter electrode plate 14, the LDH powder 40 and the added metal ions 42 move from the counter electrode plate 14 to the substrate 12 inside the surface treatment solution 16, forming a layer of the deposited LDH powder 40 and metal hydroxide 18. The voltage of the DC power supply 30 is set to a voltage required for electrophoretic deposition. In electrophoretic deposition, the charged powder is pressed onto the electrode substrate by the force of an electric field (F=qE.F: force, q: Coulomb force, E: voltage).

[0021] The operation of the electrophoretic deposition apparatus thus configured will now be described. In an electrophoretic deposition apparatus, an electric field is applied to a substrate 12, on which the powder is deposited, as the cathode, and a counter electrode plate 14, such as a stainless steel plate, as the anode. As a result, the powder and positively charged ions (cations) in the electrolyte are attracted to the cathode, and the negative ions (anions) are attracted to the anode. The powder attracted to the cathode is pressed against it by the electric field. At the same time, water is electrolyzed on the surface of the cathode, generating hydrogen and increasing the pH. As a result, the positive ions (cations) attracted to the cathode are precipitated on the cathode surface as hydroxides in a high pH environment. In the electrophoretic deposition apparatus used to manufacture a metal plate having the layered double hydroxide of the present invention on its surface, the LDH powder is pressed against the cathode Mg alloy surface by an electric field, and simultaneously, Mg ions and / or Al ions are precipitated as hydroxides due to an increase in pH, precipitated in a state adsorbed to the LDH powder, or precipitated as organometallic compounds that are compounds with organic solvents. The metal ions adsorbed to the LDH powder react with water in the air to become hydroxides or oxides, and the organometallic compounds become hydroxides or oxides when hydrolyzed. For this reason, the LDH powder can be fixed to the Mg alloy surface using the metal hydroxide as a binder (glue). In the present invention, we aim to cause the precipitation of metal ions as hydroxides in parallel, but the details of the precipitation reaction of metal ions are not known. It is currently unknown which reaction caused the metal hydroxide precipitated in the present invention to become hydroxide. The most likely scenario is a reaction between hydroxide ions generated from water and metal ions, but this has not been proven.

[0022] Layered double hydroxides are represented by the general formula: [M 2+ (1-x) M 3+ x (OH)2][A n- x / n ·yH2O] (see Eiichi Narita, Clay Science, 46(4), 207-218 (2007)). Here, the basic layer M 2+ are divalent metal ions such as Mg (magnesium), Zn (zinc), Ca (calcium), Mn (manganese), Pd (palladium), Sr (strontium), Fe (iron), Co (cobalt), Ni (nickel), and Cu (copper). Basic layer M 3+ are trivalent metal ions such as Al (aluminum), Bi (bismuth), Ga (gallium), Ni, Mn, V (vanadium), Ce (cerium), La (lanthanum), Cr (chromium), Fe (iron), Co (cobalt), and In (indium). The trivalent metal ions in the hydroxide-based layer are mixed with the divalent metal ions at a maximum molar ratio of M 2+ :M 3+ Up to 2:1 substitution is possible. The anion A in the middle layer is NO3 - ,CO3 2- ,OH - ,Cl - ,SO4 2- ,SiO4 4- or n-valent anions such as phosphate, chromate, permanganate, vanadate, selenate, borate, fluoride, carboxylate, molybdate, stannate, aluminate, and chromate. In particular, vanadate ions (VO4 3-, [VO3] n n- etc.), molybdate ion (MoO4 2- etc.), stannate ion (SnO3 2- ), aluminate ion (Al(OH)4 ― ), chromate ion (CrO4 2- ) and the like are preferably included.

[0023] The surface treatment solution 16 is an electrolyte for surface treatment, and has the following composition as an electrophoretic solution: Organic solvent-water mixed solvent: Organic solvents include alcohols such as ethanol, methanol, butanol, propanol, isopropanol, glycerin, and ethylene glycol. Ketones include acetone, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Ethers include diethyl ether. Others include dimethyl sulfoxide, dimethylformamide, and chloroform.

[0024] The concentration of the LDH powder dispersed in the electrolyte should be 0% or more and 10% or less in volume ratio to the electrolyte. If the concentration of the LDH powder exceeds 10%, the distance between the particles in the suspension becomes short, causing aggregation and making the particles more likely to settle, which is a technical problem. When metal nitrates are added as metal ions to the electrolyte, the concentration ranges of Mg(NO3)2 and Al(NO3)3 may be, for example, in the following ratio. Mg(NO3)2:Al(NO3)3=1:0-0:1 Magnesium ions adsorb to the surface of the LDH powder and migrate to the negative electrode side together with the LDH powder, where they precipitate as gel-like magnesium hydroxide on the negative electrode surface, resulting in the technical effect that the magnesium hydroxide acts as a glue to adhere the LDH powder to the negative electrode surface and to other powder particles. Aluminum ions, like magnesium ions, adsorb to the surface of the LDH powder and migrate, resulting in the technical effect that they act as a glue to adhere the LDH powder to the negative electrode surface and to other powder particles. When magnesium ions and aluminum ions are added simultaneously, they precipitate as a double hydroxide of magnesium and aluminum on the negative electrode surface, acting as a glue to adhere the LDH powder to the negative electrode surface and to other powder particles.

[0025] FIG. 2 is a flow chart illustrating the process for producing a metal plate having the layered double hydroxide of the present invention on its surface. First, metal ions are added to the electrolytic solution 16 (S100). Next, LDH powder is dispersed in the electrolytic solution 16 (S102). In this case, stirring is performed using a stirrer, for example. Alternatively, the LDH powder may be dispersed in the electrolytic solution 16 first (S102), and then the metal ions may be added to the electrolytic solution 16 (S100). The LDH powder spontaneously becomes charged in the electrolytic solution 16. Next, the electrode substrate 12 and the counter electrode plate 14 are immersed in a suspension consisting of the electrolyte 16 containing the added metal ions and the LDH powder 40 (S104). An electric field is applied between the electrode substrate 12 and the counter electrode plate 14 (S106). The electric field is applied, for example, by connecting one pole of a DC power source 30 to the substrate 12 with an electric wire 32, connecting the other pole of the DC power source 30 to the counter electrode plate 14 with an electric wire 34, and applying an electric field by a constant voltage or pulse voltage of a predetermined potential from the DC power source 30. Then, the metal ions are electrodeposited as hydroxides on the electrode substrate 12 together with the LDH powder 40 (S108). Electrophoretic deposition is continued until the thickness of the layered double hydroxide on the electrode substrate 12 reaches a predetermined value (S110). The time for which electrophoretic deposition is continued may be determined by directly measuring the thickness of the layered double hydroxide on the electrode substrate 12, or may be determined from the total amount of charge supplied from the DC power source 30 or the change in weight of the base material before and after electrophoretic deposition.

[0026] In the examples, commercially available hydrotalcite (HT) powder was used as the LDH powder. HT has CO3 between the layers. 2- This is an Mg-Al-based LDH with ions inserted. The substrates used were Mg-3mass% Al-1mass% Zn (AZ31) alloy and pure Mg plate. AZ31 alloy is a general-purpose magnesium alloy currently used in components for automobiles, cameras, personal computers, mobile phones, etc. In the following examples, layered double hydroxide layers were produced by changing the type of substrate, the type and concentration of LDH, the composition and composition ratio of the solvent, the applied voltage, and the like.

[0027] <Reference Example 1> Electrophoretic deposition of HT powder only The surface of an Mg-3mass% Al-1mass% Zn (AZ31) plate was finished with #1200 waterproof abrasive paper to prepare a substrate. A solution of commercially available hydrotalcite (HT) powder with a particle size of about 1 μm suspended at 1 to 5 w / v% (weight / volume%) in a solvent of ethanol:water = 4:1 (volume ratio) was used as the electrolyte. While stirring the suspension, the substrate AZ31 plate was inserted as the working electrode and a stainless steel mesh plate as the counter electrode. A pulse voltage of peak-to-peak (pp) voltage of 10 V, frequency of 0.1 Hz, and duty ratio of 98% was applied between the AZ31 plate as the cathode and the counter electrode for 10 minutes to perform electrophoretic deposition (EPD). The AZ31 plate after EPD was dried at 100 °C for 1 hour and then ultrasonically cleaned with an isopropanol solution to obtain an LDH-deposited surface. The surface before ultrasonic cleaning was uniformly covered with HT powder when observed visually, but most of the HT powder fell off from the substrate surface due to ultrasonic cleaning.

[0028] Figure 3 shows electron microscope images of the HT deposition surface when the HT concentration in the EPD was 1 w / v%, 2 w / v%, 3 w / v%, and 5 w / v%. Aggregates of HT powder were found to adhere to the surface. As the HT powder concentration in the electrolyte increased, the amount of HT powder adhered increased, but the HT powder fell off during ultrasonic cleaning, exposing the substrate surface, and it was not possible to adhere a sufficient amount of HT powder.

[0029] Example 2: Electrophoretic deposition of HT powder when Mg ions and / or Al ions are added to the electrolyte The substrate used was an AZ31 plate whose surface had been finished with #1200 waterproof abrasive paper. The electrolyte used was a solution in which magnesium nitrate and aluminum nitrate were dissolved in a solvent of ethanol:water = 4:1 (volume ratio) at the concentrations shown in Table 1, and commercially available HT powder with a particle size of approximately 1 μm was suspended at 3 w / v% as the LDH. Table 1 shows the Mg ion and Al ion concentrations and Mg:Al concentration ratio added to the ethanol-water electrolyte containing hydrotalcite (HT) powder, as well as the sample name. Next, while stirring the suspension, the substrate AZ31 plate was inserted as the working electrode and a stainless steel mesh plate as the counter electrode. A pulse voltage of 10 V peak-to-peak (pp) voltage, 0.1 Hz frequency, and 98% duty ratio was applied between the AZ31 plate and the counter electrode for 10 minutes to perform EPD. The AZ31 plate after EPD was dried at 100°C for 1 hour and then ultrasonically cleaned with an isopropanol solution to obtain a mixed deposition layer of LDH-metal hydroxide.

[0030] [Table 1]

[0031] Figure 4 shows an electron microscope photograph of a mixed deposit layer subjected to EPD with 3 w / v% HT powder added to the electrolyte in Table 1. Figure 4 shows that, compared with Reference Example 1 ("3% HT" in Figure 1), the amount of HT powder adhesion increased with the addition of Mg ions and / or Al ions to the electrolyte, and the substrate surface was sufficiently covered with HT powder even after ultrasonic cleaning. Figure 5 shows the X-ray diffraction patterns of the mixed deposit layer subjected to EPD with 3 w / v% HT powder added to the electrolyte in Table 1, where (A) shows the case where only Al ions or Mg ions were added, and (B) shows the case where both Mg ions and Al ions were added. XRD peaks derived from HT powder were obtained in both electrolytes. The HT powder peaks of the mixed deposit layer formed in the electrolyte with both Mg ions and Al ions added were stronger than the HT powder peaks of the mixed deposit layer formed in the electrolyte with either Mg ions or Al ions added. In addition, the mixed deposit layer formed in the electrolyte with low concentrations of Mg ions and Al ions also showed clear HT powder peaks.

[0032] The relationship between the thickness of the mixed deposition layer measured with a one-shot 3D shape measuring instrument (Keyence, detection sensitivity: 1 μm or more) and the total concentration of Mg ions and Al ions in the electrolyte is shown in Figure 6. The mixed deposition layer showed thicknesses ranging from 1 μm to 130 μm, and showed a tendency to become thicker as the Mg and Al ion concentrations in the electrolyte increased.

[0033] Example 3: Dry and wet cycle test of the sample prepared in Example 2 [Table 2]

[0034] A wet-dry cycle test was carried out on the samples shown in Table 2, which were prepared using AZ31 as the substrate. Table 2 shows the LDH-metal hydroxide mixed deposition samples used in the wet-dry cycle test. 1g / m on sample surface 2After the NaCl was attached to the sample, a wet-dry cycle test was performed in which the relative humidity around the sample was changed to 30% RH for 8 hours, 95% RH for 8 hours, and 30% RH for 8 hours, for a total of four cycles. Figure 7 shows the appearance of the LDH-metal hydroxide mixed deposition surface after the wet-dry cycle test. For comparison, a photo of the appearance of as-polished AZ31 that underwent a similar wet-dry cycle test is shown. With as-polished AZ31, corrosion occurred over the entire surface, and deep corrosion pits were observed locally. In contrast, when the sample was covered with a mixed deposition layer of HT powder, a type of LDH, and metal hydroxide, the frequency of occurrence of deep corrosion pits visible to the naked eye was significantly reduced. It was shown that the LDH-metal hydroxide mixed deposition layer acts as a corrosion-resistant coating.

[0035] Example 4: Preparation of mixed deposition layer of LDH-metal hydroxide on pure Mg substrate or AZ31 substrate and corrosion test [Table 3]

[0036] The substrates used were pure Mg and AZ31, the surfaces of which had been finished with #1200 waterproof abrasive paper. The electrolyte was prepared by dissolving magnesium nitrate and aluminum nitrate in a solvent of ethanol:water = 4:1 (volume ratio) at the concentrations shown in Table 3, and suspending commercially available HT powder with a particle size of approximately 1 μm at 5 w / v% as the LDH. Table 3 shows the LDH-metal hydroxide mixed deposition sample with a hydrotalcite (HT) powder concentration of 5% prepared for the wet-dry cycle test. While stirring the suspension, an AZ31 or pure Mg substrate was inserted as the working electrode and a stainless steel mesh plate as the counter electrode. A pulse voltage of 10 V peak-to-peak (pp) voltage and 0.1 Hz frequency was applied between the AZ31 or pure Mg substrate as the cathode and the counter electrode at a duty ratio of 98% for 10 minutes or at a duty ratio of 50% for 20 minutes to perform EPD. After EPD, the pure Mg and AZ31 substrates were dried at 100°C for 1 hour and then ultrasonically cleaned in acetone to obtain a mixed deposition layer of LDH-metal hydroxide.

[0037] A wet-dry cycle test was carried out on the samples shown in Table 3. The sample surface was coated with 1 g / m 2 After the NaCl was applied, a wet-dry cycle test was performed in which the relative humidity around the sample was changed to 30% RH for 8 hours, 95% RH for 8 hours, and 20% RH for 8 hours, for a total of four cycles. Figure 8 shows photographs of the appearance of samples before and after repeated wet-dry tests, with (A) showing a pure Mg plate and (B) showing an AZ31 plate. When coated with a mixed deposition layer of HT, a type of LDH, and metal hydroxide, the corroded area was significantly reduced to about 50%, even for pure Mg. No significant corrosion visible to the naked eye was observed for AZ31. This indicates that the prepared LDH-metal hydroxide mixed deposition layer functions as a corrosion-resistant coating regardless of the composition of the base Mg alloy.

[0038] Example 5: Preparation of a mixed deposition layer of LDH and metal hydroxide on a substrate AZ31 by constant voltage electrophoretic deposition method The substrate used was an AZ31 plate with the surface finished with #1200 waterproof abrasive paper. The electrolyte was prepared by dissolving magnesium nitrate in a solvent of isopropanol:water = 98:2 or 96:4 (volume ratio) at the concentrations shown in Table 4, and suspending commercially available HT powder with a particle size of approximately 1 μm at 4 w / v% as the LDH. Table 4 shows the Mg ion concentration added to the isopropanol-water electrolyte, the applied voltage, and the sample name. An AZ31 substrate was inserted as the working electrode and a stainless steel plate was inserted as the counter electrode. A constant voltage of 50 to 200 V was applied between the AZ31 plate as the cathode and the counter electrode for 1 minute to perform EPD. The AZ31 plate after EPD was dried at room temperature. Since the HT powder did not peel off even when the surface was lightly rubbed with a gloved hand, ultrasonic cleaning was not performed. The adhesion of the HT powder was improved by applying a higher voltage than in Examples 1 to 4. An electron microscope photograph of the mixed deposition layer is shown in Figure 9. It can be seen that a dense LDH-metal hydroxide mixed deposition layer was formed in a short time of one minute. It was shown that a homogeneous LDH-metal hydroxide mixed deposition layer can be formed by EPD at a constant voltage when the volume ratio of water in the solvent is made smaller than in Examples 2 to 4.

[0039] [Table 4]

[0040] Example 6: Preparation of mixed deposition layer of LDH-metal hydroxide containing molybdate ions on substrate pure Al or pure Fe by constant voltage electrophoretic deposition method and corrosion test Two types of substrates were used: pure Al and pure Fe. The layered double hydroxide (LDH) powder deposited on the substrate surface contained molybdate ions (MoO4 2- ) or carbonate ions (CO3 2- Two types of hydrotalcite (HT) powder containing Cr, Fe, and Fe+ were used. The surfaces of the two types of plate materials were finished with #1200 waterproof abrasive paper to prepare the substrates. The electrolyte was prepared by dissolving 0.04 mol / L magnesium nitrate and 0.01 mol / L aluminum nitrate in a solvent of isopropanol:water = 40:1 (volume ratio) and suspending MoLDH powder or HT powder at 2 w / v% (weight / volume%). The substrate was inserted as the working electrode and a stainless steel plate or carbon plate as the counter electrode into the electrolyte. A constant voltage of 100 V was applied between the substrate and the counter electrode for 1 minute to perform electrophoretic deposition (EPD). The substrate after EPD was dried at 100°C for 1 hour to obtain a mixed deposition coating sample of MoLDH powder-metal hydroxide or a mixed deposition coating sample of HT powder-metal hydroxide. The names of the samples prepared are shown in Table 5.

[0041] Electron microscope images of the MoLDH powder coating surface of pure Al and pure Fe are shown in Figure 10, and electron microscope images of the HT powder coating surface are shown in Figure 11. It can be seen that a deposition layer containing MoLDH powder or HT powder was formed on the surface. X-ray diffraction patterns of the MoLDH powder coating surface of pure Al and pure Fe are shown in Figure 12, and X-ray diffraction patterns of the HT powder coating surface are shown in Figure 13. In addition to the X-ray diffraction peaks originating from MoLDH powder and HT powder, the MoLDH powder coating surface and the HT powder coating surface showed diffraction peaks from the metal hydroxide precipitated with the powder and from the respective substrates. The diffraction peaks of the precipitated metal hydroxide appeared as shoulder peaks on the low-angle side of the diffraction peaks of MoLDH or HT, suggesting that they are a type of LDH. From the results of Figures 10 to 13, it became clear that the coating layer was composed of MoLDH powder or HT powder and LDH precipitated from the electrolyte.

[0042] [Table 5]

[0043] A wet-dry cycle test was carried out on the MoLDH or HT coated samples shown in Table 5. The sample surface was coated with 1 g / m 2 After the NaCl was applied, a wet-dry cycle test was performed in which the relative humidity around the sample was changed to RH 30% for 8 hours, RH 95% for 8 hours, and RH 30% for 8 hours, for a total of 7 cycles.

[0044] Figure 14 shows photographs of the appearance of the MoLDH powder-coated surface and the HT powder-coated surface after a wet-dry cycle test. For comparison, photographs of the appearance of uncoated pure Al and uncoated pure Fe, which were subjected to a similar wet-dry cycle test, are also shown. Discolored areas were visible on the uncoated Al surface after the wet-dry cycle test, whereas no changes visible to the naked eye were observed on the MoLDH-Al and HT-Al surfaces. Rust formed in spots all over the uncoated Fe surface, indicating that corrosion had occurred over almost the entire surface. On the other hand, rust (discolored and dark areas) was visible in some areas on the MoLDH-Fe and HT-Fe surfaces, but the area of ​​corroded areas had significantly decreased, and the corroded area was smaller on the MoLDH-Fe surface than on the HT-Fe surface.

[0045] Figure 15 shows the weight change of the samples before and after the wet-dry cycle test. In (a), pure Al was used as the substrate, and in (b), Fe was used as the substrate. The weight of uncoated Al and uncoated Fe decreased after the wet-dry cycle test, and it was found that the corrosion products were partially dissolved by washing with water after the test, resulting in a weight loss. On the other hand, the weight of the MoLDH powder or HT powder-coated samples increased after the wet-dry cycle test, and it was found that the corrosion products were not dissolved by washing with water. Therefore, for the MoLDH powder or HT powder-coated samples, the greater the weight change, the greater the amount of corrosion. For both pure Al and pure Fe, the MoLDH powder-coated samples had a smaller weight change than the HT powder-coated samples. This indicates that the MoLDH powder-coated surface containing the corrosion inhibitor is more corrosion-resistant than the HT powder-coated surface.

[0046] The results in Figures 14 and 15 show that when MoLDH containing a corrosion inhibitor such as molybdate ions was coated, the molybdate ions released from MoLDH during the dry-wet cycle test suppressed the onset or progression of corrosion of the substrates pure Al and pure Fe. Therefore, it was clarified that the method of the present invention is effective as a coating method for LDH with an inhibitor inserted between layers, and that the coated inhibitor-containing LDH coating releases the inhibitor in a corrosive environment, which is necessary for the self-repairing property to be exhibited.

[0047] According to the above embodiments 2 to 6, the following effects are obtained. (1) By using an ethanol-water mixed solvent or an isopropanol-water mixed solvent as the solvent for the electrolyte, the effect of water, which is the cause of corrosion of magnesium alloys, was reduced. Since the cathodic reaction in the corrosion reaction of magnesium alloys is a reduction reaction of water, the corrosion of magnesium alloys can be suppressed by lowering the proportion of water. In addition, the hydrogen gas generated by the reduction reaction of water can be reduced, which reduces defects in the coating. Note that organic solvents such as ethylene glycol and glycerin can also be used instead of ethanol or isopropanol. (2) In the case of the LDH layer in Reference Example 1, which was deposited in an electrolyte consisting only of an LDH powder suspended in an ethanol-water mixed solvent, most of the LDH powder fell off upon ultrasonic cleaning in acetone or isopropanol. On the other hand, in the case of the LDH powder-metal hydroxide mixed deposition layer deposited in an electrolyte containing Mg(NO3)2 and / or Al(NO3)3 added to an ethanol-water mixed solvent, a nearly uniform mixed deposition layer remained even after ultrasonic cleaning in acetone or isopropanol. This shows that the addition of metal nitrates to the electrolyte is effective in improving the adhesion of the LDH powder. (3) The LDH powder-metal hydroxide mixed deposition layer deposited at high voltage in an electrolyte of an isopropanol-water mixed solvent with a small volume ratio of water and the addition of Mg(NO3)2 did not peel off even when the EPD surface was lightly rubbed with a gloved hand. This shows that increasing the applied voltage is effective in improving the adhesion of the LDH powder-metal hydroxide mixed deposition layer. (4) The method according to the present embodiment is effective for forming a mixed deposition layer of LDH powder and metal hydroxide containing a corrosion inhibitor between the layers, and it is found that the method according to the present embodiment forms an LDH coating film with excellent corrosion resistance. [Industrial Applicability]

[0048] As explained in detail above, the method of manufacturing a metal plate having a layered double hydroxide on the surface of the present invention makes it possible to easily form a highly corrosion-resistant coating on magnesium alloys and aluminum alloys, and depending on the application, it is also possible to easily apply paint in addition to the highly corrosion-resistant coating. Therefore, when these light alloys are used in transportation equipment or home appliances, their durability is increased even when they are exposed to rain or seawater containing chloride ions or human sweat. [Explanation of symbols]

[0049] 10: Electrolytic cell 12: Substrate (metal substrate to be treated, electrode substrate) 14: Return electrode 16: Surface treatment solution (electrolyte) 18: Deposited metal hydroxides 20: Stirrer 22: Stirrer 30:DC power supply 36: Function generator 40: LDH (layered double hydroxide) powder 42:Added metal ions

Claims

1. a step of adding metal ions to an electrolytic solution containing water and dispersing a layered double hydroxide powder in the electrolytic solution, or a step of dispersing a layered double hydroxide powder in the electrolytic solution containing water and adding metal ions to the electrolytic solution; a step of immersing an electrode substrate and a counter electrode plate in a suspension composed of the electrolytic solution containing the added metal ions and the layered double hydroxide powder, the electrode substrate being a metal plate to be coated; a step of applying an electric field between the electrode substrate and the counter electrode plate to electrodeposit the metal ions as hydroxides together with the layered double hydroxide powder on the electrode substrate; The electrodeposition does not include electrodeposition of a metal from the metal ions. A method for producing a metal plate having a layered double hydroxide on its surface.

2. 2. The method for producing a metal plate having a layered double hydroxide on a surface thereof according to claim 1, wherein the electrolytic solution is a mixed solvent of an organic solvent and water.

3. 3. The method for producing a metal plate having a layered double hydroxide on a surface thereof according to claim 2, wherein the volume ratio of the organic solvent to the water is organic solvent:water=99:1 to 70:

30.

4. The method for producing a metal plate having a layered double hydroxide on a surface thereof according to claim 2 or 3, characterized in that the organic solvent includes any one of ethanol, methanol, butanol, ethanol, propanol, isopropanol, glycerin, ethylene glycol, acetone, dimethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diethyl ether, dimethyl sulfoxide, dimethylformamide, and chloroform.

5. The metal ion is any one of Mg, Al, Zn, Mn, Fe, Co, Ca, Cr, and In, The metal salt that generates the metal ion is a nitrate, sulfate, carbonate, carboxylate, phosphate or chloride. A method for producing a metal plate having the layered double hydroxide according to any one of claims 1 to 4 on its surface.

6. The layered double hydroxide powder has the general formula: [M 2+ (1-x) M 3+ x (OH) 2 ][A n- x/n ・yH 2 O], and M 2+ is a divalent metal ion selected from any one of Mg (magnesium), Zn (zinc), Ca (calcium), Mn (manganese), Pd (palladium), Sr (strontium), Fe (iron), Co (cobalt), Ni (nickel), and Cu (copper), M 3+ is a trivalent metal ion selected from any one of Al (aluminum), Bi (bismuth), Ga (gallium), Ni (nickel), Mn, V (vanadium), Ce (cerium), La (lanthanum), Cr (chromium), Fe (iron), Co (cobalt), and In (indium), The A is NO 3 - , CO 3 2- , O.H. - , Cl - , S.O. 4 2- , SiO 4 4- or an anion having a valence of n (n=1, 2, 3, or 4) selected from phosphate, chromate, permanganate, vanadate, selenate, borate, fluoride, carboxylate, stannate, aluminate, and molybdate; A method for producing a metal plate having the layered double hydroxide according to any one of claims 1 to 5 on its surface.

7. The layered double hydroxide powder contains trivalent metal ions and divalent metal ions in a maximum molar ratio of M 2+ : M 3+ 7. The method for producing a metal plate having a layered double hydroxide on a surface thereof according to claim 6, wherein the ratio of the metal to the surface of the layered double hydroxide is 2:

1.

8. the volume ratio of the layered double hydroxide powder to the metal hydroxide in the deposition layer electrodeposited on the electrode substrate is layered double hydroxide powder:metal hydroxide=90:10 to 10:90; A method for producing a metal plate having the layered double hydroxide according to claim 6 or 7 on its surface.

9. The electrode substrate is a pure Mg material, a pure Al material, a pure Fe material, an AZ31 (Mg-3Al-1Zn) alloy, an AZ91 (Mg-9Al-1Zn) alloy, an AM60 (Mg-6Al-0.4Mn) alloy, an AXM (Mg-Al-(Zn)-Ca) alloy, a WE43 (Mg-4Y-3RE) alloy, or a ZK60 (Mg-6Zn-0.5Zr) alloy, a 5000 series Al alloy (Al-Mg), a 6000 series Al alloy (Al-Mg-Si), a 7000 series Al alloy (Al-Zn-Mg) alloy, or a carbon steel; A method for producing a metal plate having the layered double hydroxide according to any one of claims 1 to 8 on its surface.

10. 10. The method for producing a metal plate having a layered double hydroxide on a surface thereof according to claim 1, wherein a constant voltage or a pulse voltage is used as the electric field applied to the electrode substrate.

11. A metal plate having a layered double hydroxide on a surface thereof, The layered double hydroxide is a mixed deposited coating of layered double hydroxide powder and metal hydroxide, The thickness of the mixed deposition coating is 0.5 μm or more and 130 μm or less. A metal plate having a layered double hydroxide on a surface thereof, The mixed deposition coating is characterized in that no metal of the metal hydroxide is electrodeposited on the mixed deposition coating. A metal plate having a layered double hydroxide on its surface.

12. 12. The metal plate having a layered double hydroxide on a surface thereof according to claim 11, wherein the metal plate is selected from the group consisting of pure Mg material, pure Al material, pure Fe material, AZ31 (Mg-3Al-1Zn) alloy, AZ91 (Mg-9Al-1Zn) alloy, AM60 (Mg-6Al-0.4Mn) alloy, AXM (Mg-Al-(Zn)-Ca) alloy, WE43 (Mg-4Y-3RE) alloy, ZK60 (Mg-6Zn-0.5Zr) alloy, 5000 series Al alloy (Al-Mg), 6000 series Al alloy (Al-Mg-Si), 7000 series Al alloy (Al-Zn-Mg) alloy, and carbon steel.

13. The layered double hydroxide powder has the general formula: [M 2+ (1-x) M 3+ x (OH) 2 ][A n- x/n ・yH 2 O], and M 2+ is a divalent metal ion selected from any one of Mg (magnesium), Zn (zinc), Ca (calcium), Mn (manganese), Pd (palladium), Sr (strontium), Fe (iron), Co (cobalt), Ni (nickel), and Cu (copper), M 3+ is a trivalent metal ion selected from any one of Al (aluminum), Bi (bismuth), Ga (gallium), Ni (nickel), Mn, V (vanadium), Ce (cerium), La (lanthanum), Cr (chromium), Fe (iron), Co (cobalt), and In (indium), The A is NO 3 - , CO 3 2- , O.H. - , Cl - , S.O. 4 2- , SiO 4 4- or an anion having a valence of n (n=1, 2, 3, or 4) selected from phosphate, chromate, permanganate, vanadate, selenate, borate, fluoride, carboxylate, stannate, aluminate, and molybdate; A metal plate having the layered double hydroxide according to claim 11 or 12 on its surface.

14. A metal plate having a surface thereof comprising the layered double hydroxide according to any one of claims 11 to 13, characterized in that the volume ratio of the layered double hydroxide powder to the metal hydroxide in the mixed deposited coating of the layered double hydroxide powder and the metal hydroxide is layered double hydroxide powder:metal hydroxide = 90:10 to 10:90.

Citation Information

Patent Citations

  • Solar energy collector

    JP1980017024A

  • Electrode for cell and its manufacturing method

    JP1986010855A

  • The nickel coating is deposited on a metallic base material and a nickel oxide - - oxide

    JP1990500602A

  • A method for coating a metal surface with a coating composition containing layered double hydroxide particles.

    JP2015520018A

  • Functional electrode and method for producing the same

    JP2019502016A